Theory and technology of preventing water from flooding roadways - CAO, Sheng-gen; HOU, Shi-song; LI, Zhong-hua (Journal of China University of Mining and Technology, 2008)
According to the principle of effective stress action of rock and soil, we established a mechanical model of water flooding into roadways, analyzed the constitutive relation of hydrodynamic pressure and contact pressure of rock and soil and discovered that the process of pre-grouting of a roadway curtain is a dynamically balancing process in which effective stress keeps gradually increasing and pore water pressure gradually declines. In such a grouting process, the initial water plugging effect is realized when the effective stress and total stress reaches equilibrium. A rigid-flexible packing layer is designed behind the brickwork to increase the effective stress and reduce pore water pressure in order to have a permanent water proof performance. This provides a theoretical basis for roadway driving and permanent water prevention. The monitoring and application results show that the initial and permanent waterproof theory has provided an effective method for roadway driving and making it waterproof.